A Historical Overview of the Evolution of Emotional Intelligence - Gawai, Milind (Ushus Journal of Business Management, 2016)
Emotions have been a subject of study for ages. Many great thinkers have critically analysed emotions and built various theories - some of them complimentary, emphasising the importance of emotions as inextricable aspects of human life, and yet many criticising the pernicious influence emotions could have if not tempered with reason. The 19th century witnessed several empirical studies on emotions, and we find a scientific approach towards understanding the different dimensions of emotions. Presently, ‘Emotional Intelligence’, also referred to as ‘Emotional Quotient’, has gained significant attention in the world of business. Organisational leaders have realised the importance of Emotional Intelligence and its contribution to the success and growth of an organisation. This paper attempts to chronicle the significant milestones in the development of the concept of ‘Emotional Intelligence,’ tracing its origin from the pioneers to the present time.